THE ENHANCEMENT OF COMMUNICATION AND INFERENCE SKILLS IN BUFFER AND HYDROLYSIS LESSON BY PROBLEM SOLVING LEARNING - febriani febriani; ratu betta rudibyani; chansyanah diawati (Universitas Lampung, 2012)
The objective of this research is to describe effectiveness of the learning model of problem solving in improving communication and inference skills in buffer and hydrolysis lesson. Samples in this research were students of State Senior High School 1 Tumijajar of classes XI Sciences 2 and XI Sciences 3 even semester School Year 2011-2012 that have equal academic abilities. This research used a quasi experiment method with Nonequivalent Control Group Design. Effectiveness of the learning model of problem solving was measured by significant differences in control class and experiment class, shown by significant gain. Based on the results of this research, average value of N-gain for communication skills in control and experiment class were 0,53 and 0,65; and average value of N-gain for inference skills in control and experiment class were 58 and 0,66. Hypothesis testing in this research used test two average different with t-test. Hypothesis result test show that class that used learning model of problem solving had higher communication and inference skills than class with conventional learning model. This indicated that learning model of problem solving was effective to improving communication and inference skills in buffer and hydrolysis lesson. Keywords: learning model of problem solving, communication skills and inference skills